Microplastic accumulation patterns and transfer of benzo[a]pyrene to adult zebrafish (Danio rerio) gills and zebrafish embryos - Batel, Annika; Erdinger, Lothar; Braunbeck, Thomas (Environmental pollution, 2018)
Since only a few studies have investigated effects of microplastics (MPs) by routes other than ingestion, this study was designed to analyze the accumulation patterns and transfer of toxic substances associated with microplastic exposure by simple attachment to (1) adult zebrafish (Danio rerio) gills and (2) zebrafish embryos. Two sizes of fluorescently labelled polymers (1-5 and 10-20μm) loaded with the model polycyclic aromatic hydrocarbon (PAH) benzo[a]pyrene (BaP) were used to analyze fate, accumulation and transfer of microplastic-associated persistent organic pollutants (POPs) on gills and embryos. Results indicate that microplastics did not permanently accumulate at high amounts in adult zebrafish gills after 6 nor 24h of incubation: Most particles only superficially adhered to the mucus layer on the filaments, which is constantly being excreted. In contrast, the smaller and heavier MPs (1-5μm) accumulated in high numbers on the surface of zebrafish egg chorions. In both exposure scenarios, transfer of BaP could be visualized with fluorescence microscopy: A prominent BaP signal was visible both in gill filaments and arches after 6 and 24h incubation and in zebrafish embryos after exposure to BaP-spiked microplastics. Furthermore, the gill EROD (Ethoxyresorufin-O-deethylase) assay showed a clear trend to CYP 1A (Cytochrom P450 1 A) induction via exposure to BaP-spiked microplastics. However, BaP from spiked microplastics did not reach sufficiently high concentrations to be able to induce morphological effects in the fish embryo toxicity test (FET). In contrast, control exposure to waterborne BaP did induce effects in the FET. As a conclusion, microplastics can also transfer POPs not only via ingestion, but also by simple attachment to epithelia or via the water column. However, further studies are needed to clarify if these interactions are of environmental concern relative to waterborne exposure to toxic substances.